Musical participation and positive youth development in middle school - Ilari, Beatriz; Cho, Eun (Frontiers in Psychology, 2023)
This study examined positive youth development (PYD), school connectedness, and hopeful future expectations in middle school students (N=120) with four levels of musical participation in school-based and extracurricular music programs.. Levels of participation were based on students’ engagement in different music programs, including the Virtual Middle School Music Enrichment (VMSME), a tuition-free, extracurricular program that focuses on popular music education and virtual learning. We also investigated student musical listening preferences, musical tuition, and daily instrumental practicing. Study participants completed an anonymous, online survey that contained five self-report measures including the very- brief form of the PYD questionnaire, a subscale of school connectedness, and a scale of hopeful future expectations. Findings revealed significant differences in PYD scores by grade and gender, and associations between levels of musical participation and competence, a PYD component. Liking music and participation in extracurricular activities predicted scores on school connectedness, and starting formal music education before age 8 predicted scores in hopeful future expectations. We also found VMSME students to stem from neighborhoods with lower HDI than students in the other study groups, which points to issues of access to formal music education. Findings are discussed in light of earlier research on PYD, extracurricular activities in adolescence, the ubiquity and functions of music in adolescence, and deficit thinking in education .